Avaliação do desenvolvimento infantil em Programas de Saúde da Família - Sigolo, Ana Regina Lucato (2011)
This paper aimed to determine the contribution of development screening instrument in the reporting from parents on child assessment accomplished in the Family Health Program. Thereunto it was proposed the following specific objectives: 1) to locate a screening tool for development in the literature, appointed by it as the most relevant and appropriate, based on reports from parents, in order to identify possible signs of risk for the development (step 1), 2) to verify types of notes in medical records (step 2) and if nature of these notes changes after doctors had knowledge of the research objectives (step 3), 3) to verify if there is a discrepancy among information contained in records of the child and those provided by the instrument from reported information by the person responsible for implementation of the instrument (step 4), 4) to evaluate, with physicians and nurses from the Family Health Program, the contribution of introducing an assessment of development based on evaluation of parents to identify signs of risk in development (step 5). Participated this research five doctors, five nurses, 60 parents/ children‟s guardians aged zero to two years attended in five units from Family Health Program. In step 1, through documentary research, it was selected an existent tool on the literature for screening of child development. The steps 2 and 3 were to medical records analysis of 12 children attended in each unit (60 records at each step) in a period before and after (respectively) of knowledge research objectives by doctors. In step 4, it was conducted interviews with families and application of instrument selected with parents / guardians of 12 children attended in each unit. In step five, doctors and nurses were interviewed about the adequacy and functionality of the instrument. It analyzed qualitative and quantitative results according previously defined with classes of response, categories and subcategories. It was hoped thereby to verify the utility of this practice in the Family Health Units and thus it contribute to the early detection of children‟s development delays in public health system. As a result of step 1 was accomplished an adaptation of the instrument defined "File Monitoring of Development" proposed by the Health Ministry. In steps 2 and 3 can be observed prevalence of health complaints and medical behaviors also related to health in medical records and there was no difference in the nature of medical notes after the knowledge of the goals of searching for them. In step 4, the results showed that 38 of 60 (63.34%) children who didn‟t show a normal development for their age, their medical records didn‟t have any information regarding the risk/delay detected by the instrument. And in step 5, 66.67% of respondents said that information provided by parents had to be considered complementary to the evaluation of the child, because in most cases, weren‟t totally reliable information. However, everybody reported to be possible to introduce into the routine of the Family Health Program evaluation procedures of child development, even with existence of some difficulties, this practice is keeping fundamental importance in child health.